Accretion, Soft and Hard Collision: Similarities, Differences and an Application from the Newfoundland Appalachian Orogen - van Staal, Cees; Zagorevski, Alexandre (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2020)
We argue there is no distinction between accretion and collision as a process, except when accretion is used in the sense of incorporating small bodies of sedimentary and/or volcanic rocks into an accretionary wedge by off-scraping or underplating. There is also a distinction when these terms are used in classifying mountain belts into accretionary and collisional orogens, although such classifications are commonly based on a qualitative assessment of the scale and nature of the accreted terranes and continents involved in formation of mountain belts.Soft collisions occur when contractional deformation and associated metamorphism are principally concentrated in rocks of the leading edge of the partially pulled-down buoyant plate and the upper plate forearc terrane. Several young arc-continent collisions show evidence for partial or wholesale subduction of the forearc such that the arc is structurally juxtaposed directly against lower plate rocks. This process may explain the poor preservation of forearcs in the geological record. Soft collisions generally change into hard collisions over time, except if the collision is rapidly followed by formation of a new subduction zone due to step-back or polarity reversal. Thickening and metamorphism of the arc's suprastructure and retro-arc part of upper plate due to contractional deformation and burial are the characteristics of a hard collision or an advancing Andean-type margin. Strong rheological coupling of the converging plates and lower and upper crust in the down-going continental margin promotes a hard collision.Application of the soft–hard terminology supports a structural juxtaposition of the Taconic soft collision recorded in the Humber margin of western Newfoundland with a hard collision recorded in the adjacent Dashwoods block. It is postulated that Dashwoods was translated dextrally along the Cabot-Baie Verte fault system from a position to the north of Newfoundland where the Notre Dame arc collided ca. 10 m.y. earlier with a wide promontory in a hyperextended segment of the Laurentian margin.